Islamic Economic Student’s Knowledge and Attitude Toward Halal Pharmacy Product in East Java, Indonesia - Rusmita, Sylva Alif; Ryandono, Muhamad Nafik Hadi; Filianti, Dian; Mohd Salleh, Marhanum Che (al-Uqud : Journal of Islamic Economics, 2021)
A Muslim has a limitation in consuming or wearing something. A Muslim is only permitted to consume something halal, either in food, drink, clothes, even finance. In the pharmaceutical industry, the standard of Halal Pharmaceutical is the most crucial document that should be followed to standardize the quality and the safety of halal. This research will analyze the knowledge and attitude of Islamic economics students who have the basic knowledge about halal and analyze how their attitude to the halal pharmacy. The research method is qualitative, with a literature review and descriptive analysis data from the questioner. Information on the label will influence the choices before buying and or consuming the medicine on the customer site. Consumers prefer to choose medicine with a halal label so that it will also benefit industries that have halal labels. But, in halal pharmacy, customers still hard to applied halal things in medicine; even though customers understand about halal, customers' attitude does not imply the principle of halal in the medicine.